Urgensi Pengaturan Private Military Contractors (PMCs) Dalam Hukum Humaniter Internasional - Liminanto, Elvira; Wattimena, Josina Augustina Yvonne; Peilouw, Johanis Steny Franco (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Private Military Contractors (PMCs) are private companies engaged in providing professional security and military services for profit. The involvement of its members in armed conflicts often results in unclear status in international humanitarian law, many assume that the PMC is the same as mercenaries. So we need in-depth analysis to distinguish the status of the two.Purposes of the Research: To analyze the working time has been regulated in International Humanitarian Law, and the position of Private Military Contractors (PMCs) in International Humanitarian Law.Methods of the Research: The method used is normative legal research. The research approach is a statutory approach and a conceptual approach. Sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials is through literature study and then analyzed through a perspective using qualitative methods.Results of the Research: The results showed that the regulation on mercenaries explicitly existed only in Additional Protocol I of 1977. However, in fact, provisions that resemble mercenaries have been regulated in the 1907 Hague Convention and regulated in Geneva Convention III 1949 in this convention the term mercenary has been included. (Mercenary). The unclear legal status of PMCs members, especially when working in situations of armed conflict, puts them in a gray area which has the potential to cause debate about their presence in an armed conflict which also impacts the protection of their human rights. So far, many parties have identified members of Private Military Contractors (PMCs) with mercenaries, so that a stigma has emerged that calls them "reincarnations" of mercenaries (mercenaries / soldier of fortune / dogs of war). However, the concept of mercenaries as contained in Article 47 of Additional Protocol II 1977 cannot be applied optimally to PMCs, especially to determine their legal status when serving in situations of armed conflict.